Experimental study of heat and mass transfer of Solar Powered liquid desiccant regeneration system (University of Khartoum Engineering Journal, 2022)
Liquid desiccant regeneration has an important effect on the performance of a liquid desiccant airconditioning system. Instead of a conventional packed regenerator an internally heated regenerator is proposed toachieve better regeneration performance. This paper presents an experimental investigation on the performance ofthe internally heated counter flow desiccant regeneration system. Triethylene Glycol (TEG) solution is used as theworking desiccant material in this system. The structured packing used in this system was a finned tube heatexchanger. The effects of inlet parameters such as air flow rate, relative humidity, desiccant solution flow rate anddesiccant solution concentration on the performance of the system are studied. The performance of the system isevaluated using the water evaporation rate, regenerator effectiveness, and enthalpy effectiveness.